Transurethral Resection of Prostate using Bipolar System: A Comparison with Monopolar System - Islam, Mohammad Hasibul; Bhuiyan, N I; Faruque, Mohammad Salahuddin; Morshed, Md Selim; Rana, Md Masud; Islam, Ashraful (Bangladesh Journal of Urology, 2025)
Background: Benign Enlargement of the Prostate (BEP), common in ageing males, leads to lower urinary tract symptoms (LUTS) due to BEP-related obstruction (BPO). Monopolar Transurethral Resection of the Prostate (M-TURP) is the traditional "gold standard" surgical approach, but it has drawbacks like fluid absorption-related complications. Bipolar Transurethral Resection of the Prostate (B-TURP) emerged as an alternative with advantages, including lower sodium drop and reduced TUR syndrome risk. However, debates persist regarding haemoglobin drop, sodium change, and resection rate differences. This study compares M-TURP and B-TURP, evaluating efficacy through resection rate, postoperative parameters, and safety by monitoring serum sodium, haemoglobin, TUR syndrome, catheterization time, and hospital stay. Aim of the study: The study aimed to evaluate the safety and efficacy of the bipolar with monopolar technique for the endoscopic resection of the prostate. Methods: This is a one-year Randomized Control Trial (RCT) conducted at Square Hospitals Ltd in Dhaka, from December 2020 to November 2021. The study involved 60 patients with BEP who underwent either Monopolar or Bipolar Transurethral Resection of the Prostate (TURP). Group A (control) underwent Monopolar TURP, while Group B (experimental) underwent Bipolar TURP. Inclusion criteria included age ≥ 50 and symptomatic BEP with surgical indications. Data was collected, and results were analyzed using statistical software. Parameters such as serum haemoglobin, serum sodium, resection rate, catheterization & hospitalization time, maximum flow rate, and complications were compared, with statistical significance set at P ≤ 0.05. Result: The study compared outcomes of monopolar transurethral resection of the prostate (M-TURP) and bipolar transurethral resection ot the prostate (B-TURP). Baseline variables showed no significant differences between groups. Intraoperatively, resected prostate volume was similar, but B-TURP had a slightly faster resection rate, but not significant. Postoperatively, M-TURP exhibited higher decreases in serum haemoglobin and sodium levels. Clot retention incidence was 10% in M-TURP and 0% in B-TURP, though statistically insignificant. Catheterization and hospital stays were shorter in B-TURP. A six-week follow-up revealed no significant inter-group differences in IPSS and maximum flow rate improvement. Conclusion: Comparing the findings of the present study, it can be concluded that bipolar transurethral resection is safer than monopolar transurethral resection and has similar efficacy in managing benign enlargement of the prostate. Bangladesh J. Urol. 2024; 27(1): 23-32